Alcances de la Norma Anti- Elusiva Específica Aplicable a la Reorganización de Sociedades - Tori Vargas, Fernando (2014)
This paper analyses national and international background of the anti-avoidance rule described in article 105-A of such law, its scope and its relationship with corporate reorganizations’ Peruvian income tax regime. In addition, the article will cover the discussion on the relationship between general anti-avoidance rule and specific anti-avoidance rules.